2006
DOI: 10.1002/cbf.1308
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and total antioxidant status in patients with breast cancer

Abstract: Oxidative stress is considered to be involved in the pathophysiology of all cancers. The aim of this study is to examine oxidative stress and antioxidant status in patients with breast cancer by evaluation of the serum levels of total antioxidant capacity (TAC) and lipid peroxidation products as malondialdehyde (MDA) and lipid hydroperoxide and to investigate the relationship between these parameters, oxidative stress and serum lipids and lipoproteins. In our study, serum TAC, MDA, lipid hydroperoxide, HDL-cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 20 publications
8
34
1
Order By: Relevance
“…8 Several studies have found enhanced lipid peroxidation and depletion of antioxidants in the plasma of BC patients, suggesting that increased oxidative stress may be related to human breast carcinogenesis. [9][10][11][12][13] Moreover, an increased content of lipid peroxidation products was found in BC tissue, supporting the hypothesis of breast tumorigenesis by in situ oxidative stress. 14,15 On the other hand, recent reports suggest that lipid peroxidation may represent a protective mechanism in BC through the induction of apoptosis, thereby maintaining the balance between breast epithelial cell growth and death, 8,16 supporting the hypothesis that lipid peroxidation in tissue of benign breast disease (BBD) is greater than in BC.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…8 Several studies have found enhanced lipid peroxidation and depletion of antioxidants in the plasma of BC patients, suggesting that increased oxidative stress may be related to human breast carcinogenesis. [9][10][11][12][13] Moreover, an increased content of lipid peroxidation products was found in BC tissue, supporting the hypothesis of breast tumorigenesis by in situ oxidative stress. 14,15 On the other hand, recent reports suggest that lipid peroxidation may represent a protective mechanism in BC through the induction of apoptosis, thereby maintaining the balance between breast epithelial cell growth and death, 8,16 supporting the hypothesis that lipid peroxidation in tissue of benign breast disease (BBD) is greater than in BC.…”
supporting
confidence: 69%
“…Although several lipid peroxidation products have been previously identified in plasma and tissues of women with breast disease, as well as in human milk, [9][10][11][12][13][14][15][16]23,24 we report for the first time the detection of both MDA and 8-iso-PGF 2a , 2 major indexes of lipid peroxidation and oxidative stress, in NAF from healthy women and patients with BC. [4][5][6][7] We found that breast milk from healthy women contains lower levels of MDA than matched plasma, postulating that this difference may be related to different metabolism of free fatty acids (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the salivary concentrations of TAC and MDA in the PTC patients were respectively lower and higher compared to the control subjects. Consistent with our findings, Sener et al reported significantly lower levels of TAC in breast cancer patients compared to the control group (17). Furthermore, Hosseini-Zijoud et al demonstrated significantly lower TAC concentrations in the patients medullary thyroid cancer compared to healthy controls, which could be due to the consumption of antioxidants as a result of augmented metabolism and production of free radicals (8).…”
Section: Discussionsupporting
confidence: 90%
“…Several reports exist that reveal increases in MDA concentration in patients presenting neoplasm (Thangaraju et al 1994;Ray et al 2000;Sener et al 2007). It has also been reported that lipid peroxidation in breast cancer tissues was enhanced compared to nonmalignant tissues (Tas et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of data obtained by Sener et al (2007) showed that lower total antioxidant capacity and higher malondialdehyde (MDA) levels increased oxidative stress and could be related to breast cancer.…”
Section: Introductionmentioning
confidence: 99%